ANALISIS PERBANDINGAN KARAKTER REMAJA YANG DIASUH OLEH IBU YANG BEKERJA DI RUMAH DENGAN IBU YANG BEKERJA DI LUAR RUMAH DI KOTA PALOPO - YUNUS YUNUS; ARHANUDDIN ARHANUDDIN (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2018)
The family is the first and primary environment for the development of a child. In the family of a child undergoing a process of socialization for the first time, which in the process of a child is introduced and taught various grades of life are very useful and crucial for a child's development in the future. The formation of adolescent characters in villages Songka depending on the parents' parenting. Teenage characters are formed by mothers who work at home, children are more disciplined while teenage characters by mothers who work outside the home less disciplined but independent, creative, take initiative.2) Advantages and disadvantages of teenage characters are cared for by mothers who work at home tend to be disciplined. Moderate weakness is depressed child, lack of confidence, and sometimes become unmanageable. Medium teenagers are cared for bymothers work outside the home is the child to be independent, to have good relationships with friends, while the children are not familiar shortcomings pressured by their parents to do something, generally grow as someone who is quite satisfied and high ambitions, Solutions to overcome deficiencies in parenting teenage characters who work at home mothers and mothers who work outside the home in the Village Songka. Mothers who work at home, should spend more time and communicate about everything with his teenage children to feel cared for and loved. While the mothers work outside the home should take advantage of a limited time with his teenage children to do activities together that can instill discipline and responsibility. Keywords: Parents, Character, Youth.